Pengaruh Pengetahuan dan Kesadaran Muzakki Terhadap Keputusan Membayar Zakat di Baznas Kabupaten Sorong - Siti Alfajriyani; Andi Hasrun (Prodi Ekonomi Syariah IAIN Sorong, 2022)
The main problem in this study is whether the knowledge and awareness of muzakki affect the decision to pay zakat at BAZNAS, Sorong Regency. This study aims: 1) To determine the effect of muzakki knowledge on the decision to pay zakat in BAZNAS, Sorong Regency. 2) To determine the effect of muzakki awareness on the decision to pay zakat in BAZNAS, Sorong Regency. 3) To determine the effect of knowledge and awareness of muzakki on the decision to pay zakat in BAZNAS, Sorong Regency. The type of research used is a type of quantitative research whose results are calculated using analysis techniques and classical assumption tests, multiple linear regression and hypothesis testing with the help of SPSS version 28. The approach used is a correlation approach. The sample used is 54 respondents who have paid zakat at BAZNAS Sorong Regency using a questionnaire (quisionery). Based on the results of the study, it shows that knowledge and awareness of muzakki have a positive and significant effect on the decision to pay zakat in BAZNAS, Sorong Regency. The most influential and significant variable is seen from the value of the coefficient of partial determination, namely the muzakki awareness factor. Knowledge and awareness of muzakki influence the decision to pay zakat at BAZNAS, Sorong Regency. The contribution of the independent variable to the dependent variable is 0.504 or 50.4%. The implication of this research for BAZNAS Sorong Regency is to make activities or socialization related to zakat and BAZNAS institutions so that the public knows about BAZNAS so they can decide to pay zakat at BAZNAS Sorong Regency.